2003
DOI: 10.1093/molbev/msg071
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Oxidase, an Ancient Bioenergetic Enzyme

Abstract: Operons coding for the enzyme arsenite oxidase have been detected in the genomes from Archaea and Bacteria by Blast searches using the amino acid sequences of the respective enzyme characterized in two different beta-proteobacteria as templates. Sequence analyses show that in all these species, arsenite oxidase is transported over the cytoplasmic membrane via the tat system and most probably remains membrane attached by an N-terminal transmembrane helix of the Rieske subunit. The biochemical and biophysical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 28 publications
8
105
1
5
Order By: Relevance
“…Our results indicate that haloarchaea have conserved arsenic metabolic mechanisms that are traces of the ancestors that prevailed in ancient Earth. The AioA phylogenetic analyses presented in this work challenge the current hypothesis of an origin of arsenite oxidases before the divergence of Archaea and Bacteria (Lebrun et al, 2003). In light of these results, we consider that further work is needed to better understand the antiquity and origin of the arsenic metabolism.…”
Section: Arsenic Bioenergetics In Haloarchaea Biofilmssupporting
confidence: 52%
See 1 more Smart Citation
“…Our results indicate that haloarchaea have conserved arsenic metabolic mechanisms that are traces of the ancestors that prevailed in ancient Earth. The AioA phylogenetic analyses presented in this work challenge the current hypothesis of an origin of arsenite oxidases before the divergence of Archaea and Bacteria (Lebrun et al, 2003). In light of these results, we consider that further work is needed to better understand the antiquity and origin of the arsenic metabolism.…”
Section: Arsenic Bioenergetics In Haloarchaea Biofilmssupporting
confidence: 52%
“…However, several other inorganic substrates seem to have been used in bioenergetic redox reactions in the last universal common ancestor based on the evolutionary analyses of key enzymes involved in these processes (Schoepp-Cothenet et al, 2012). Such is the case of arsenite (As(III)), which is proposed as a candidate electron donor, feeding bioenergetic chains in primordial life based on phylogenetic analysis of large subunit of arsenite oxidases (AioA) and paleogeochemical analyses (Lebrun et al, 2003;van Lis et al, 2013;Sforna et al, 2014). In fact, the arsenic seems to have been present at much higher concentrations in the ancient Earth's crust than it is today (Oremland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic oxidation is mainly used by microorganisms as a detoxification strategy, although there have been isolated bacteria that use As in their metabolic processes linked to cellular respiration and energy conservation [84]. Biotic oxidation of As is mediated by enzymes known as arsenite oxidases, such as AroA/B, AsoA/B, and AoxA/B [85][86][87]. Likewise, other microorganisms can also catalyze the reduction of arsenate to arsenite [88].…”
Section: Arsenic-bearing Ores Bioleachingmentioning
confidence: 99%
“…The large subunit (AroA~90 kDa) of the arsenite oxidase is the first example of a new subgroup of the dimethylsulfoxide (DMSO) reductase family of molybdoenzymes (Ellis et al, 2001). It is reported that this heterodimeric enzyme is located on the outer surface of the inner membrane, and is transported to the cytoplasmic membrane (Lebrun et al, 2003). The arsenite oxidase gene has been used as genetic marker of As(III) oxidation (Hamamura et al, 2009).…”
Section: As(iii)-oxidizing Bacteriamentioning
confidence: 99%